2012
DOI: 10.1007/s12282-012-0407-5
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of diabetic mastopathy: MR imaging and pathological correlation

Abstract: Diabetic mastopathy is a rare benign condition associated with long-standing diabetes mellitus and presents with breast lumps. This report describes two cases in which diffusion-weighted images (DWI) on magnetic resonance imaging were quite different from each other. In case 1, there were hyperintense lesions on DWI, and surgically removed specimens revealed ductitis with marked lymphocytic infiltration. In case 2, no abnormal intensity was depicted on DWI, and biopsy specimens showed dense stromal fibrosis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…[13] However, the mass may have a hypersignal diffusion which does not allow to immediately exclude a malignant process. [14] After injection of contrast agent, we have demonstrated in our case a gradual enhancement in favor of benignity with a type I enhancement curve also reported by Sakuhara et al, [15] tunckbilec [16] and costantini. [13] However, diabetic mastopathy may have all malignancy criteria at MRI, i.e., hypersignal diffusion with a decrease in ADC coefficient and massive and early enhancement with a type III enhancement curve.…”
Section: Discussionsupporting
confidence: 87%
“…[13] However, the mass may have a hypersignal diffusion which does not allow to immediately exclude a malignant process. [14] After injection of contrast agent, we have demonstrated in our case a gradual enhancement in favor of benignity with a type I enhancement curve also reported by Sakuhara et al, [15] tunckbilec [16] and costantini. [13] However, diabetic mastopathy may have all malignancy criteria at MRI, i.e., hypersignal diffusion with a decrease in ADC coefficient and massive and early enhancement with a type III enhancement curve.…”
Section: Discussionsupporting
confidence: 87%
“…In the magnetic resonance spectrum, the choline peak was absent in the type 1 imaging uptake curve and the proton spectrum. Despite the improvement of imaging techniques, there are still great challenges in the diagnosis of diabetic breast disease[ 9 , 21 - 23 ]. An increasing number of studies have reported cases of diabetic breast disease complicated with malignant tumors[ 24 , 25 ], and some studies[ 26 , 27 ] have also shown that neither clinical examination nor imaging studies can clearly distinguish diabetic breast disease from breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results are also in agreement with those of other studies, which report cases of dense breasts without findings or unspecific findings such as focal asymmetry, not suspected in isolation. 2,7,11,20,23,24 MRI features have been scarcely reported in SLL, usually in scattered case reports. MRI is not always useful for differentiating SLL from cancer, as both may present overlapping findings.…”
Section: Discussionmentioning
confidence: 99%